2007
DOI: 10.1111/j.1365-2486.2007.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbon accrual in afforested agricultural soils

Abstract: Afforestation of agricultural lands can provide economically and environmentally realistic C storage to mitigate for elevated CO 2 until other actions such as reduced fossil fuel use can be taken. Soil carbon sequestration following afforestation of agricultural land ranges from losses to substantial annual gains. The present understanding of the controlling factors is inadequate for understanding ecosystem dynamics, modeling global change and for policy decision-makers. Our study found that planting agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 41 publications
5
68
0
1
Order By: Relevance
“…Consistently with our data, in other studies soil N concentration in the shallow layer was lower in agricultural lands than in Betula and Larix thinned closed canopy plantations and in Populus stands (Ritter et al, 2007;Sartori et al, 2007). Lower soil N was also detected in agricultural lands than in deciduous forests by Morris et al (2007). By contrast, soil N decreases were reported under Pinus and Eucalyptus afforestations (Binkley and Resh, 1999;Berthrong et al, 2009).…”
Section: Chemical Parameterssupporting
confidence: 80%
“…Consistently with our data, in other studies soil N concentration in the shallow layer was lower in agricultural lands than in Betula and Larix thinned closed canopy plantations and in Populus stands (Ritter et al, 2007;Sartori et al, 2007). Lower soil N was also detected in agricultural lands than in deciduous forests by Morris et al (2007). By contrast, soil N decreases were reported under Pinus and Eucalyptus afforestations (Binkley and Resh, 1999;Berthrong et al, 2009).…”
Section: Chemical Parameterssupporting
confidence: 80%
“…In addition to the influence that the chemical composition of plant residues has on the process of decomposition and incorporation of SOM, Morris et al (2007) showed that soil characteristics have a strong influence on the dynamics of carbon accumulation. Those authors found that the availability of calcium and nitrogen were strongly associated with higher carbon storage in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors observed increases in TN stocks after the conversion of land into agroforestry systems (Sartori et al, 2007;Morris et al, 2007), while others reported decreases in TN stocks upon conversion (Smal & Olszewska, 2008). The low TN stocks could be related to low plant residue input, the accumulation of the aerial parts of plants and the lack of N fertilization, while the high stocks could be related to plant residue sedimentation and atmospheric N (Mao et al, 2010).…”
Section: Total Soil Nitrogen Levels and Stocksmentioning
confidence: 99%